The Five Essential Laws of Effective Communication for Arabic Speaking Skills at Islamic Universities in Thailand - Taufiq, Muhammad; Yulia, Fatma; Harahap, Laila Rahimah; Mila, Rohsidah (Institut Agama Islam Negeri Palangka Raya, 2024)
Numerous studies on the teaching of speaking skills have been conducted; however, the majority have primarily focused on analyzing instructional models, strategies, and methods. The aspect of instructional communication, particularly when examined through the framework of the Five Inevitable Laws of Effective Communication, has yet to be thoroughly explored in previous research. Therefore, this study aims to measure the communication effectiveness of Maharah Kalam learning at an Islamic university in Thailand based on these five laws, also known as the REACH concept: Respect, Empathy, Audibility, Clarity, and Humility. This study employed a mixed-methods approach, collecting qualitative data through interviews and quantitative data through questionnaires to evaluate the effectiveness of communication in Arabic speaking skills learning. For the qualitative aspect, interviews were conducted to gather data. In terms of the quantitative aspect, validity and reliability tests were performed. Validity was assessed using the Product Moment Correlation formula, while reliability was measured using Cronbach's Alpha for internal consistency. The results indicated that the effectiveness of Arabic speaking skills communication among students at Kolej Islam Syeikh Daud AlFathani (KISDA) reached 82%, placing it in the